2014
DOI: 10.1002/rcm.6973
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic analysis of N2O produced in a conventional wastewater treatment system operated under different aeration conditions

Abstract: Under the highest aeration condition, NH2OH oxidation (nitrification) was the main contributor to N2O production at about 90% and 57%, respectively, at the aeration tank middle and end. At other sampling points, 55-63% of the N2O was produced by bacterial NO2(-) reduction (nitrifier-denitrification) with a lower nitrification contribution. For all sampling points in the lower aeration experiments, NO2(-) reduction was a major N2O production pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Based on this mapping approach, most of data was fallen near to NO 2 -reduction suggesting that the nitrifierdenitrification was dominant pathway to N 2 O production. This is agreed with previous results that found nitrifierdenitrification was a key process for N 2 O production in aerobic tank of CAS system applied in Japanese WWTP [11,12]. The contribution of this pathway is estimated as 87-99% at stations N1-1, N1-4 and N5-4, respectively.…”
Section: Concentrations Of Dissolved Inorganic Nitrogen (Din) Compounsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on this mapping approach, most of data was fallen near to NO 2 -reduction suggesting that the nitrifierdenitrification was dominant pathway to N 2 O production. This is agreed with previous results that found nitrifierdenitrification was a key process for N 2 O production in aerobic tank of CAS system applied in Japanese WWTP [11,12]. The contribution of this pathway is estimated as 87-99% at stations N1-1, N1-4 and N5-4, respectively.…”
Section: Concentrations Of Dissolved Inorganic Nitrogen (Din) Compounsupporting
confidence: 92%
“…Using this technique, Sutka et al [8][9][10] found that the SP for N 2 O from hydroxylamine oxidation (~33‰) and nitrite reduction (~0‰) differs in a pure culture study and noted that this difference can be used to distinguish the relative contributions of nitrification and denitrification sources to N 2 O emissions. There have still been only several reported studies which applied this measurement technique to field N 2 O samples [11,12] or referred to the relative contributions of nitrification and denitrification. To our knowledge, the present study is the first to (1) apply the stable isotopic analysis to the determination of N 2 O sources during the case of WWTS in Mongolia and to (2) understand the actual contributions of nitrification and denitrification to N 2 O production.…”
Section: Introductionmentioning
confidence: 99%
“…In general, N 2 O concentration is higher and δ 15 N and δ 18 O are lower in aerobic water than in anaerobic water; those features possibly reflect the process that occur under each condition: nitrification and denitrification. The SP value observed in aerobic process tanks of a WWTP indicated that N 2 O was produced by nitrifier denitrification (Yoshinari & Wahlen, 1985; Townsend‐Small et al, ; Toyoda et al, ; Wunderlin et al, ; Tumendelger, Toyoda, & Yoshida, ). Table presents the reported isotopic signature of N 2 O from human sewage treatment processes.…”
Section: N2o Isotopocules In Various Environmentsmentioning
confidence: 99%
“…The water quality, energy consumption, cost, and N 2 O production in MLE processes for nitrogen removal depend on two operational parameters; the aeration rate in the aerobic tank and the internal recycle flow (IRF) rate from the aerobic to the anoxic tank (Jimenez et al 2011;Tumendelger et al 2014). The aeration rate in the aerobic tank determines the gas-liquid equilibrium between the dissolved and gaseous N 2 O.…”
Section: Introductionmentioning
confidence: 99%